OXYGEN UPTAKE IN THE BRINE SHRIMP ARTEMIA IN RELATION TO SALINITY - Dwivedi, S N; Iftekhar, M B (Indian Journal of Fisheries, 2011)
The rate of oxygen consumption of Artemia has decreased with decrease in salinity and in freshwater the 02 consumed was least. The probable reasons for such decrease have (been discussed